Thick Film Transducers for High Frequency Coded Ultrasonography - NOWICKI, Andrzej; LEWANDOWSKI, Marcin; WÓJCIK, Janusz; TYMKIEWICZ, Ryszard; LOU–MOLLER, Rasmus; WOLNY, Wanda; ZAWADA, Tomasz (Archives of Acoustics, 2011)
Recently a new technology of piezoelectric transducers based on PZT thick filmhas been developed as a response to a call for devices working at higher frequen-cies suitable for production in large numbers at low cost. Eight PZT thick filmbased focused transducers with resonant frequency close to 40 MHz were fabricatedand experimentally investigated. The PZT thick films were deposited on acousticallyengineered ceramic substrates by pad printing. Considering high frequency and non-linear propagation it has been decided to evaluate the axial pressure field emitted(and reflected by thick metal plate) by each of concave transducer differing in radiusof curvature – 11 mm, 12 mm, 15 mm, 16 mm.All transducers were activated using AVTEC AVG-3A-PS transmitter and Ritecdiplexer connected directly to Agilent 54641D oscilloscope. As anticipated, in allcases the focal distance was up to 10% closer to the transducer face than the onerelated to the curvature radius. Axial pressure distributions were also compared tothe calculated ones (with the experimentally determined boundary conditions) usingthe angular spectrum method including nonlinear propagation in water. The com-puted results are in a very good agreement with the experimental ones. The trans-ducers were excited with Golay coded sequences at 35–40 MHz. Introducing thecoded excitation allowed replacing the short-burst transmission at 20 MHz withthe same peak amplitude pressure, but with almost double center frequency, result-ing in considerably better axial resolution. The thick films exhibited at least 30%bandwidth broadening comparing to the standard PZ 27 transducer, resulting in anincrease in matching filtering output by a factor of 1.4–1.5 and finally resulting ina SNR gain of the same order.